Predominance of Lactobacillus plantarum Strains in Peruvian Amazonian Fruits - Sanchez, J (2019)
The objective of this research was the identification and characterization of lactic acid bacteria (LAB) isolated from Peruvian Amazonian fruits. Thirty-seven isolates were obtained from diverse Amazonian fruits. Molecular characterization of the isolates was performed by ARDRA, 16S-23S ITS RFLP and rep-PCR using GTG5 primers. Identification was carried out by sequencing the 16S rDNA gene. Phenotypic characterization included nutritional, physiological and antimicrobial resistance tests. Molecular characterization by Amplified Ribosomal DNA Restriction Analysis (ARDRA) and 16S-23S ITS RFLP resulted in four restriction profiles while GTG5 analysis showed 14 banding patterns. Based on the 16S rDNA gene sequence, the isolates were identified as Lactobacillus plantarum (75.7%), Weissella cibaria (13.5%), Lactobacillus brevis (8.1%), and Weissella confusa (2.7%). Phenotypic characterization showed that most of the isolates were homofermen-tative bacilli, able to ferment glucose, maltose, cellobiose, and fructose and grow in a broad range of temperatures and pH. The isolates were highly susceptible to ampicillin, amoxicillin, clindamycin, chloramphenicol, erythromicyn, penicillin, and tetracycline and showed great resistance to kanamycin, gentamycin, streptomycin, sulfamethoxazole/trimethoprim, and vancomycin. No proteolytic or amylolytic activity was detected. L. plantarum strains produce lactic acid in higher concentrations and Weissella strains produce exopolymers only from sucrose. Molecular methods allowed to accurately identify the LAB isolates from the Peruvian Amazonian fruits, while phenotypic methods provided information about their metabolism, physiology and other characteristics that may be useful in future biotechnological processes. Further research will focus especially on the study of L. plantarum strains.